PERLINDUNGAN HUKUM TERHADAP KONSUMEN E-COMMERCE DAN EKSISTENSI ELECTRONIC SIGNATURE DALAM PERDAGANGAN INTERNASIONAL - Putri Wasundari, Ni Putu; Thomas Lamury Hadjon, Edward (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
The development of international trade is inseparable from the development oftechnology. Its influence can be seen through the use of electronic transactionshereinafter referred to as e-commerce. In the e-commerce, consumers are the mostoften injured, therefore arrangements that provide legal protection to consumers whoconduct e-commerce is needed. Besides e-commerce, electronic signature is also knownas a tool which serves to maintain the security of the data or information transmitted.However the current rules of international trade law on e-commerce and electronicsignature are only set in the UNCITRAL Model Law. This paper aims to analyze theform of legal protection to consumers who conduct e-commerce transactions. Thispaper also want to describe the existence of electronic signatures in international tradelaw. This writing is a normative legal research that uses statute approach.
Keywords: Transactions, E-Commerce, Electronic Signature, International Trade Law